Morphofunctional Feature of the Formed Elements of Blood Cells and the Central Lymphoid Organ Under Conditions of Short-Term Hypothermic Exposure - Aminov, Ruslan (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):292